Evolution free-boundary problem for a stationary system of the theory of elasticity - Krasnoshchok, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider an evolution free-boundary problem for a stationary linear system of the theory of elasticity that arises in the investigation of solid thin films in microelectronic devices. We prove its solvability on an arbitrary time interval under the condition that the initial data are sufficiently close to the stationary solution.